Review and evaluation of current adaptation strategies for climate change on the Mekong River Delta (MRD) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
Findings from this case study (led by IPSARD and PIRCCA) supported the general technical solutions mentioned in the strategy for restructuring the rice sector. Two years after its issuance, the strategy has resulted in some initial positive impacts. Rice production in MRD has developed in a more sustainable way with increasing proportion of fragrant and specialty rice. The small farmer large fields model has increased, and there is higher adoption of improved practices. Rice production also shows higher efficiency.